Expert System for Diagnosing Pests and Diseases in Arabica Coffee Plants using the Certainty Factor Method - Era Pelita Sinaga (Institute of Computer Science, 2020)
Arabica coffee is coffee which is known to have the best quality among others, because it has a distinctive aroma and taste. However, arabica coffee is more susceptible to infection with pests and diseases, which causes farmers to experience difficulties in maintaining arabica coffee and lack of knowledge about how to control pests and diseases that attack arabica coffee. In handling pests and diseases, an agricultural consultant is needed to diagnose pests and diseases of arabica coffee plants. In this study, the expert system diagnosed pests and diseases in Arabica coffee plants was built to diagnose pests and diseases that attack arabica coffee plants, and provide solutions for pests and diseases. The method used in this expert system is the Certainty Factor method. Certainty Factor method is chosen because this method is suitable in the process of determining the identification of pests and diseases, and the results of applying this method are percentages. The percentage of expert system consultations was taken from the highest yield, as an alternative to pests and diseases that attacked arabica coffee plants. The expert system diagnoses pests and diseases of arabica coffee plants to make it easier for Arabica coffee farmers to find more detailed and accurate information about Arabica Coffee pests and diseases and their control.